Bilateral Accessory (Aberrant) Renal Arteries Associated With Uncontrolled Hypertension—Role of Renin-Angiotensin-Aldosterone Antagonist Drugs for Treatment Goal: : A Case Report - Akpunonu, Basil (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.